Contract Law : a Comparison of Civil Law and Common Law Jurisdictions. - Smyth, Claire-Michelle (Business law and corporate risk management collection., 2018)
This text serves as an accessible introduction to the law of contract. The headings chosen for examination track the main points in the lifetime of a contract--from its formation, drafting, and onward to its eventual dissolution, whether this occurs due to the terms of the contract, the will of the parties, or because of a breach of the agreed terms. It also provides studies of other notable areas within the subject, such as third-party rights, damages, and equitable remedies. In distinction to other guides to contract law, this text provides a comparative analysis of the area, incorporating sources drawn from both the civil law tradition, characteristic of several nations within Continental Europe, as well as the Anglo-American common law tradition, with cases and legislation drawn from England and the United States of America. It also explores contract law in the unique context of so-called hybrid jurisdictions--those which incorporate elements of both the common law and civilian traditions; chosen for study here are exemplary jurisdictions represented by the American state of Louisiana and Scotland in the United Kingdom. As business assumes a global dimension, knowledge of the operation of contract law across various legal traditions and national contexts is increasingly at a premium. This text enables the student to gain a coherent vision of contract law across a wide range of legal and theoretical frameworks, as well as to speak confidently when discussing the intricacies of the subject. It is at once an introductory text, as well as a reference text, which students and professionals alike can consult in the course of their studies and future careers.